The stickman's hollow [videorecording (DVD)] - Cox, Jack (Film director); Cadrot, Thomas; Simpson, Jason; Adamthwaite, Michael (Leomark Studios, 2026)
A remote wilderness hides a dark legend as Clara Hall, a young girl consumed by demonic possession, unleashes terror. A family's trip uncovers the pagan curse of Stickman's Hollow and the horrifying truth buried within.